Experimental analysis of tribological characteristics of aluminium hybrid composites fabricated by using stir casting techniques. (2021) - Preethi, V.; Daniel Das, A.; Nithyapathi, C.
Abstract: This paper focuses on the fabrication of the Aluminium hybrid composite because of its high flexibility properties. The aim of this project is to enhance the wear properties by enhancing the Wear resistance of Aluminium alloy by adding the different reinforcement. The reinforcement used here is that Alumina and CSC (Coconut Shell Charcoal) of varying proportions is fabricated using the stir casting techniques. The wear behaviour of the sample is then tested using Pin-On-Disc apparatus by considering the corresponding process parameters such as Load, Speed, and Time. The microstructure analysis is also carried out using the inverted microscope and thereby revealing that there is the proper distribution of the reinforcements.